Bacteremia caused by Actinomyces - Salazar, Raúl (1997)
We report the case of a 72-years-old woman who complains fever, headache, malaise and weakness, with a history of tooth extraction five days before the onset of this symptoms. On laboratory samples, Actinomyces israelii was isolated from her blood culture. We suggest that, although bacteremia caused by this organism is uncommon, it should be take in account, specially in febrile patients who were underwent an odontologic procedure.